The Whites - Price, Richard 1949- (Bloomsbury, 2015)
"Back in the bad old days, when Billy Graves worked for an anti-crime unit in Harlem known as the Wild Geese, the NYPD branded him as a cowboy. Now forty, he has somehow survived and become a sergeant in Manhattan Night Watch. Mostly, his team of detectives conducts a series of holding actions...and after years in police purgatory, Billy is content simply to do his job. But soon after he gets a 3:00 a.m. call about the fatal knifing of a drunk in a Third Avenue pub, his investigation moves beyond the usual handoff to the day shift. And when he discovers that the victim was once a suspect in the unsolved murder of a 13-year-old girl, he finds himself drawn back to the late 1990s when the Wild Geese were at their most wayward. Before the case can be closed, it will severely test Billy's new sense of purpose and force him to accept that his troubled past isn't past at all. Richard Price, one of America's most gifted novelists, has always written brilliantly about cops, criminals, and New York City. Now, writing as Harry Brandt, he is poised to win a huge following among all those who hunger for first-rate crime fiction"..